2005
DOI: 10.1007/s10741-005-5249-1
|View full text |Cite
|
Sign up to set email alerts
|

Thick Filament Proteins and Performance in Human Heart Failure

Abstract: Modifications in thick filament protein content and performance are thought to underlie contraction-relaxation dysfunction in human heart failure. It has been found that myofibrillar Mg.ATPase is reduced in failing myocardium, which may be due in part to the reduction in alpha-myosin heavy chain (MHC) isoform content from approximately 5-10% in normal myocardium to <2% in failing myocardium. The physiological importance of this seemingly small amount of alpha-MHC appears substantiated by the development of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 107 publications
(237 reference statements)
2
41
0
Order By: Relevance
“…33 We have also observed a low level of MyBP-C and troponin I phosphorylation in both failing heart 17,31 and myectomy muscle samples. 34 An increase in ALC-1 content in ventricular myosin from less than 5% in donor heart to 2-27% in hypertrophic and failing heart muscle has been reported, 27,35 comparable with our finding of 11% in donor and 20% in myectomy muscle. We did not examine the amount of a and bMHC isoforms present, however an investigation by Noguchi et al 36 showed that the in vitro motility sliding speed was not different in failing and donor heart myosin despite a variation of the proportion of aMHC from 0 to 13%.…”
Section: Myosin From Myectomy Muscle Is Functionally Abnormalsupporting
confidence: 90%
See 1 more Smart Citation
“…33 We have also observed a low level of MyBP-C and troponin I phosphorylation in both failing heart 17,31 and myectomy muscle samples. 34 An increase in ALC-1 content in ventricular myosin from less than 5% in donor heart to 2-27% in hypertrophic and failing heart muscle has been reported, 27,35 comparable with our finding of 11% in donor and 20% in myectomy muscle. We did not examine the amount of a and bMHC isoforms present, however an investigation by Noguchi et al 36 showed that the in vitro motility sliding speed was not different in failing and donor heart myosin despite a variation of the proportion of aMHC from 0 to 13%.…”
Section: Myosin From Myectomy Muscle Is Functionally Abnormalsupporting
confidence: 90%
“…As the combination of increased expression of ALC-1 and decreased phosphorylation of MLC-2, troponin I, and MyBP-C is commonly observed in failing heart muscle, 17,33,35 it appears that the contractile proteins in myectomy muscle are modified in a similar manner to failing heart. This is compatible with our observations that in both myocytes and in vitro motility assays contractility is similarly dysfunctional in myectomy and failing heart samples ( Figures 1 and 3).…”
Section: Myosin From Myectomy Muscle Is Functionally Abnormalmentioning
confidence: 99%
“…After birth, the α-type myosin heavy chain (α-MHC), which has a higher ATPase activity and shortening velocity, is predominant in the ventricles while β-MHC is suppressed (49). However, several stimuli are able to modify this transcriptional pattern, with β-MHC gene expression often being induced together with other genes of the fetal program during cellular remodeling.…”
Section: Molecular Substrate For Contractile Dysfunctionmentioning
confidence: 99%
“…However, several stimuli are able to modify this transcriptional pattern, with β-MHC gene expression often being induced together with other genes of the fetal program during cellular remodeling. As a result, myocytes exhibit slower shortening velocity and impaired relaxation, which could contribute, at least in part, to contractile dysfunction (49). During relaxation, most of the cytosolic Ca 2+ is rapidly taken up by SR vesicles, and a smaller amount is secreted through the sarcolemma membrane by a membrane anchored ATPase.…”
Section: Molecular Substrate For Contractile Dysfunctionmentioning
confidence: 99%
“…Although the human heart primarily possesses ␤-MHC, this finding is germane to the human heart, because nonfailing human hearts are believed to contain between 5% and 10% ␣-MHC compared with 0% to 2% present in failing heart. 10 Moreover, demonstrating that ER activation blunts ␣-to ␤-MHC switching in response to hypertension could potentially explain the greater hypertrophic reserve observed in female rodent hearts in response to pressure overload. The conversion of ␣-to…”
mentioning
confidence: 99%